Bolometric detection of terahertz quantum cascade laser radiation with graphene-plasmonic antenna arrays. (27th March 2017) - Degl'Innocenti, Riccardo; Xiao, Long; Kindness, Stephen J; Kamboj, Varun S; Wei, Binbin; Braeuninger-Weimer, Philipp; Nakanishi, Kenichi; Aria, Adrianus I; Hofmann, Stephan; Beere, Harvey E; Ritchie, David A
Abstract: We present a fast room temperature terahertz detector based on graphene loaded plasmonic antenna arrays. The antenna elements, which are arranged in series and are shorted by graphene, are contacting source and drain metallic pads, thus providing both the optical resonant element and the electrodes. The distance between the antenna's arms of approximately 300 nm allows a strong field enhancement in the graphene region, when the incident radiation is resonant with the antennas. The current passing through the source and drain is dependent on the graphene's conductivity, which is modified by the power impinging onto the detector as well as from the biasing back-gate voltage. The incident radiation power is thus translated into a current modification, with the main detection mechanism being attributed to the bolometric effect. The device has been characterized and tested with two bound to continuum terahertz quantum cascade lasers emitting at a single frequency around 2 THz and 2.7 THz yielding a maximum responsivity of 2 mA W −1 .